A química supramolecular de complexos pirazólicos - Godoy Netto, Adelino Vieira de [UNESP]; Frem, Regina Célia Galvão [UNESP]; Mauro, Antonio Eduardo [UNESP] (Sociedade Brasileira de Química, 2008)
The purpose of this review is to describe the progress in the supramolecular chemistry of the pyrazolyl-based metal complexes. The text is written under the structural point of view, emphasizing the role of the covalent and non-covalent interactions in the rational construction of super and supramolecules.
Supramolecular chemistry of pyrazolyl complexes
Keywords: pyrazolyl transition metal compounds; covalent and non-covalent interactions; supramolecular architectures